A case of systemic lupus erythematosus with sideroblastic anaemia terminating in erythroleukaemia. Issue 4 (August 1981) - Ng, H S; Ng, H W; Sinniah, R; Feng, P H
Abstract : A case of systemic lupus erythematosus is described in which for 10 years the only significant findings were erythema multiforme and vasculitis. Gross hepatosplenomegaly with persistent pancytopenia developed, and bone marrow examination revealed the presence of sideroblasts. The patient's condition deteriorated, and subsequently she developed a severe bleeding tendency, terminating in erythroleukaemia.